Il ghiacciaio Strandline (Baia Terra Nova, Antartide). The Strandline Glacier, Terra Nova Bay, Antarctica. - BARONI, CARLO; OROMBELLI G. (1987)
The 'Strandline Glacier is a small local alpine glacier (0.79 km-) on the coast of Gerlache Inlet, Terra Nova Bay, Victoria Land. It is a cold glacier with accumulation and ablation areas controlled by wind and irregularly distributed. The main ablation area coincides with the terminal convex zone, crossed by transverse and splaying crevasses. The AAR is of about 0.8. The front of the glacier in the central part is an ice cliff 25 m high, changing laterally into a short dome and ramp margin. The foliation is well evident along the frontal margin, showing a syncline structure. A small and discontinuous apron of snow and ice is present at the foot of the ice cliff . Inner moraines, ice cored moraines and a sheet of basal melt out till (sublimation till) are present along the marginal zone, partially resting on Holocene raised beaches. Two Holocene ice advances, possibly younger than 4 500 yr B.P., can be recognized. The front of the glacier advanced of more than 60 m the first time and about 50 m the second time, the two advances being separated by a consistent lapse of time, judging from weathering and lichen development. The glacier is presently in a retreat phase, although small push moraines near the front document minor recent advances.